A Preliminary Assessment of Paint and Coating Debris in SW Atlantic Port Areas Impacted by Boat Maintenance Activities - Islas, María Soledad (2024)
Port maintenance activities emit paint and coating particles, primarily polymeric but also containing metals like Cu and Zn, into the environment. This study examines the presence of paint/coating microparticles and their association with metal pollution in subtidal sediments from a port area in Mar del Plata, Argentina, where various boat maintenance and shipyard activities occur. Seasonal sampling was conducted at two sites diﬀering in proximity to ship maintenance activities (ST1 nearby and ST2 600 m away). Micro brittle-colored particle debris from subtidal sediments were obtained through wet sieving, quantifed, and characterized by size ( > 500 and 500-100 µm), color, atomic (SEM-EDX), and polymer (ATR-FTIR) composition. Zn levels in sediments were measured by atomic absorption. Additionally, paint particles from the marine area/shipyard were collected and characterized. Total brittle-colored particles (per Kg of dry weight sediment) were higher in ST1 (17576±8407) compared to ST2 (5758±820) considering all seasons (P< 0.05). Particles in the range 100-500 µm represent 92.7% of total. From this, 39.7% corresponds to red, 16.6% to orange, 13.9% to blue and 11.0% to green. SEM-EDS analysis showed that Zn and Cu are present in 4 and 3 particles, respectively, from sediment (n=55), and in 7 particles each from a marine area/shipyard (n=24). Average Zn levels in sediments across the two sites and seasons was 17.6 ± 9.7 mg/kg dry weight with higher concentrations at ST1 in all seasons (P< 0.05). ATR-FTIR analysis of 69 particles identifed compounds like acrylic, styrene, silicon, TiO2, phthalates, and azo colorants. Epoxy polymer was only found in marine/shipyard paint particles. These preliminary results suggest that boat maintenance facilities may be a source of brittle-colored polymeric particles, correlating with Zn levels in sediments. Further studies on various types of microparticles are needed.